From humble leadership to prosocial voice: The role of creative self-efficacy - Hendryadi Hendryadi (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
This study aims to examine the relationship between leader humility and prosocial voice by investigating the mediating role of creative self-efficacy. Drawing on social cognitive theory, the research proposes that humble leaders enhance employees' confidence in their creative capabilities, which, in turn, motivates them to engage in prosocial voice—the voluntary expression of ideas or suggestions aimed at benefiting others or the collective. A quantitative research design was employed, using a multi-wave survey method involving 382 participants. The hypothesized relationships were tested using structural equation modeling to assess both direct and indirect effects. The results reveal that leader humility positively affects creative self-efficacy, and creative self-efficacy positively affects prosocial voice. Furthermore, creative self-efficacy fully mediates the relationship between leader humility and prosocial voice, indicating that humble leadership influences employee voice entirely through strengthening employees' confidence in their creative abilities.